2018
DOI: 10.3762/bjoc.14.259
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative and reductive cyclization in stiff dithienylethenes

Abstract: The electrochemical behavior of stiff dithienylethenes, undergoing double bond isomerization in addition to ring-closure, has been investigated. Electrochromism was observed in almost all cases, with the major pathway being the oxidatively induced cyclization of the open isomers. The influence of the ring size (to lock the reactive antiparallel conformation) as well as substituents (to modulate the redox potential) on the electrocyclization was examined. In the series of derivatives with 6-membered rings, both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 48 publications
0
15
1
Order By: Relevance
“…[13,26,36] However this result stand in sharp contrast with the electrochemical behavior of others DTE pyridinium derivatives reported in the literature, as dithiazolylethenes, [11,14] which show two reversible reduction waves attributed to the successive formation of mono-(DTE *À ) and doubly-reduced (DTE 2À ) derivatives. [14,25] Similarly, two electron-reduction waves were seen for the open and closed isomers of DTEs bearing strongly electron-withdrawing substituents such as benzonitrile. [25] In light of these quite different observations and conclusions, we were keen to thoroughly investigate and provide a clear-cut attribution of the chemical steps coupled to the oneelectron reduction observed of 1 c 2 + .…”
Section: Chemphyschem Electrogenerated 1 Omentioning
confidence: 92%
See 2 more Smart Citations
“…[13,26,36] However this result stand in sharp contrast with the electrochemical behavior of others DTE pyridinium derivatives reported in the literature, as dithiazolylethenes, [11,14] which show two reversible reduction waves attributed to the successive formation of mono-(DTE *À ) and doubly-reduced (DTE 2À ) derivatives. [14,25] Similarly, two electron-reduction waves were seen for the open and closed isomers of DTEs bearing strongly electron-withdrawing substituents such as benzonitrile. [25] In light of these quite different observations and conclusions, we were keen to thoroughly investigate and provide a clear-cut attribution of the chemical steps coupled to the oneelectron reduction observed of 1 c 2 + .…”
Section: Chemphyschem Electrogenerated 1 Omentioning
confidence: 92%
“…[14,25] Similarly, two electron-reduction waves were seen for the open and closed isomers of DTEs bearing strongly electron-withdrawing substituents such as benzonitrile. [25] In light of these quite different observations and conclusions, we were keen to thoroughly investigate and provide a clear-cut attribution of the chemical steps coupled to the oneelectron reduction observed of 1 c 2 + .…”
Section: Chemphyschem Electrogenerated 1 Omentioning
confidence: 92%
See 1 more Smart Citation
“…To date, most studies have focused on the electron-rich dithienylethenes and their oxidation induced ring-closing or ring-opening reaction depending on their substitution patterns. [3][4][5][6][7][8][9][10][11] In comparison, examples of reductive electrocyclization are rare and generally require the presence of strong electron withdrawing groups such as N-methylpyridinium connected to the photochromic dithienylethene or dithiazolylethene core. [12][13][14] However, recent works showed that dithienylethenes with appropriate cyano-substitution or an extended π system could also lead to reductive ring-closure, albeit with much more negative potentials.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] However, recent works showed that dithienylethenes with appropriate cyano-substitution or an extended π system could also lead to reductive ring-closure, albeit with much more negative potentials. [11] It is worth noting that in most cases the redox input triggers only one-way isomerization and cannot be used to bring the diarylethene back to its initial state. There are only few reports on bidirectional photo-and redox-switchable diarylethenes.…”
Section: Introductionmentioning
confidence: 99%